2015
DOI: 10.1007/s10126-015-9668-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile Analysis of miR-221 and miR-222 in Different Tissues and Head Kidney Cells of Cynoglossus semilaevis, Following Pathogen Infection

Abstract: Half-smooth tongue sole (Cynoglossus semilaevis) is an important marine commercial fish species in China, which suffers from widespread disease outbreaks. Recently, in this regard, our group identified immune-related microRNAs (miRNAs) of C. semilaevis following Vibrio anguillarum infection. Furthermore, miRNA microarray was utilized to characterize the immune roles of important miRNA candidates in response to bacterial infection. Therefore, in the present study, we characterized miR-221 and miR-222 and profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Although it was reported that several miRNAs are involved in regulating IBDV replication by targeting viral genomic RNA or host cell proteins (Wang et al, 2013 ; Ouyang et al, 2015 ), the effect of miRNAs on IBDV replication and the underlying mechanisms are still unclear. In this study, we evaluated the miRNA expression profile in DF-1 cells in response to IBDV infection and selected 11 candidate miRNAs for further analysis, and the 11 candidate miRNAs play important roles in host immunity (Gu et al, 2015 ; Hosokawa et al, 2015 ; Lamontagne et al, 2015 ; Lind et al, 2015 ; Tan et al, 2015 ; Wu et al, 2015 ; Gonzalez-Martin et al, 2016 ; Peng et al, 2016 ; Yan et al, 2016 ; Liang et al, 2017 ; Liu et al, 2017 ). Through TCID 50 assay, we found that only gga-miR-155 significantly suppressed IBDV replication.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was reported that several miRNAs are involved in regulating IBDV replication by targeting viral genomic RNA or host cell proteins (Wang et al, 2013 ; Ouyang et al, 2015 ), the effect of miRNAs on IBDV replication and the underlying mechanisms are still unclear. In this study, we evaluated the miRNA expression profile in DF-1 cells in response to IBDV infection and selected 11 candidate miRNAs for further analysis, and the 11 candidate miRNAs play important roles in host immunity (Gu et al, 2015 ; Hosokawa et al, 2015 ; Lamontagne et al, 2015 ; Lind et al, 2015 ; Tan et al, 2015 ; Wu et al, 2015 ; Gonzalez-Martin et al, 2016 ; Peng et al, 2016 ; Yan et al, 2016 ; Liang et al, 2017 ; Liu et al, 2017 ). Through TCID 50 assay, we found that only gga-miR-155 significantly suppressed IBDV replication.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, studies have revealed that the expression of miR-221 is up-regulated in several types of cancers and was related to cancer cell proliferation [60][61][62]. Yan et al [63] evaluated the expression of miR-221 in half-smooth tongue sole after challenge with V. anguillarum, and a head kidney cell line stimulated with different PAMPs. Similar to our study, the expression of miR-221 was increased in the liver and spleen of the infected sole, and the in vitro study indicated that both LPS and pIC up-regulated the expression of miR-221 at 6 h post-stimulation [63].…”
Section: Mirnas Associated With Both Antiviral and Antibacterial Immumentioning
confidence: 99%
“…Yan et al [63] evaluated the expression of miR-221 in half-smooth tongue sole after challenge with V. anguillarum, and a head kidney cell line stimulated with different PAMPs. Similar to our study, the expression of miR-221 was increased in the liver and spleen of the infected sole, and the in vitro study indicated that both LPS and pIC up-regulated the expression of miR-221 at 6 h post-stimulation [63]. The expression of miR-221-5p was also evaluated in olive flounder in response to VHSV infection, showing increased transcription 24 h post-injection [58].…”
Section: Mirnas Associated With Both Antiviral and Antibacterial Immumentioning
confidence: 99%
“…A combination of upregulated and downregulated miRNAs was chosen for RT-qPCR, as well as miRNAs involved in vertebrate immune responses and macrophage function (31,70,71). In addition, we examined immune-relevant miRNAs that were identified by RNA-seq but not DE to confirm their presence in fish EVs: the fish-specific ssa-miR-2188-3p, as well as ssa-miR-21a-5p, ssa-miR-150-5p, and ssa-miR-221-5p, which are all virus responsive miRNAs in teleost fish, and involved in mammalian macrophage activation and/or differentiation (37,(72)(73)(74)(75). All nine miRNAs that were detected by RNA-seq were also detected by RT-qPCR.…”
Section: Rt-qpcr Analysis Confirmed Mirna Abundance In Day 1 and Day mentioning
confidence: 99%
“…Again, this may in part be due to a different group of fish being used for RNA-seq and RT-qPCR. At the cellular level, miR-21a is involved in macrophage activation and immune response in both mammals and fish [33,72,73]. MiR-21 deficient mice had decreased expression of M1 macrophage markers and enhanced expression of M2 markers, while transfection of a miR-21 mimic enhanced M1 markers and decreased M2 markers (95).…”
Section: The Highly Abundant Mir-21a Is Associated With Macrophage Acmentioning
confidence: 99%